IMPLEMENTASI ASAS ITIKAD BAIK DALAM KONTRAK PADA TRANSAKSI BISNIS DIGITAL - Maulidina Sari; Aveciena Yoe; Nurul Laylan Hsb; Moh. Hamzah (Yurisprudentia: Jurnal Hukum Ekonomi, 2026)
Electronic contracts have gained recognition as legal instruments in the Indonesian legal system. However, the implementation of the principle of good faith in digital business transactions still faces various challenges, such as an imbalance in the position of the parties, the use of standard clauses that tend to be one-sided, and the increased risk of misuse and leakage of personal data. This condition shows that there is a gap between normative arrangements and contractual practices in the digital space which has implications for legal certainty, justice, and legal protection for the parties. This research aims to analyze the implementation of the principle of good faith based on Article 1338 paragraph (3) of the Civil Code and examine the legal consequences and forms of accountability for violations of this principle in digital business transactions. The research uses normative juridical methods with legislative, conceptual, and case approaches. The results of the study show that the principle of good faith has evolved from the concept of subjective honesty to an objective standard that demands transparency, information disclosure, personal data protection, and a balance of rights and obligations of the parties at all stages of the contractual relationship. However, its implementation is still constrained by the disproportionate use of standard clauses, unilateral cancellation of transactions, weak personal data protection, and suboptimal supervision of digital business actors. Violations of the principle of good faith can cause legal consequences in the form of default, unlawful acts, the obligation to pay compensation, and administrative sanctions in accordance with the provisions of laws and regulations. Therefore, it is necessary to strengthen regulations, increase business compliance by business actors, and more effective supervision to realize legal certainty, justice, and trust in the digital business ecosystem in Indonesia.